Reconstructing Economic Self-Determination from the Third World Approach to International Law - M. Yakub Aiyub Kadir (International Law Department, Faculty of Law Universitas Padjadjaran, 2023)
International Law governing the relationship between states has been considered failed in reformatting the principle of economic self-determination (ESD) as a continual link of political self-determination in the post decolonisation era. Such situation has placed the principle to be a vague concept in terms of its meaning and application in current international law. Such situation has contributed to continual economic dependency of the Third World (TW) states on the first world as considered the more developed states. TW states face difficulty to develop their argument to demonstrate people national interest in current international economic context. Having utilised doctrinal and TWAIL approach, this paper argues that there has been a potential meaning of ESD which can be developed from fragmentation of documents in international law, particularly in the United Nations General Assembly Resolutions (UNGA resolutions), the Law of State Succession and the International Human Rights law. This meaning then shapes the fragmented sources to be a principle for TW to be used in their international economic relation, particularly in settling economic dispute relations with Western states.